Another History in Psychology: A Women’s Trio - Winkler Müller, María Inés; Magaña Frade, Irene; Wolff Reyes, Ximena (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
The history of psychology, subspecialty that has increased in relevance includes critical historiographic positions that point to be the notorious absence of women’s contributions in the discipline’s reconstruction, making power and gender bias evident in dominant discourse. Partial results of a major research rescue the contribution of three women whose works merit a more explicit and potent recognition effort from the one received until now. Biographical aspects are summarized in connection with the work and scientific production of Mary Whiton Calkins (1883-1930), pioneer of the last century; the Swiss Bärbel Inhelder, whose career evolved together with Jean Piaget; and the Canadian Joan Mowat Erikson (emigre to the USA), whose intellectual production appears concealed within her husband’s. Specific aspects of each trajectory are highlighted, confirming the presence of sociocultural factors that rended possible gender discrimination such as the minimization of their theoretical and experimental contributions or their elimination from history.